Preparation, characterization, and structural studies of new sodium gallium tungstate phosphate glasses - Lodi, Thiago A.; Galleani, Gustavo; Junior, Marcos de Oliveira; Santagneli, Silvia H. [UNESP]; Eckert, Hellmut; de Camargo, Andrea S.S. (My University, 2023)
A new glass forming region in the quaternary system Na2O-P2O5-WO3-Ga2O3 along the composition line (NaPO3)80-x(Ga2O3)20(Na2WO4)x (x = 0, 5, 10, 15, 20 and 25 mol%) has been prepared and characterized by X-ray diffraction, Differential Scanning Calorimetry (DSC), Raman scattering and 31P, 23Na and 71Ga nuclear magnetic single and double resonance NMR techniques. The partial substitution of the NaPO3 component by Na2WO4 produces a significant increase of molar volume (decreased oxygen packing density), whereas the glass transition temperatures Tg pass through a shallow maximum near x = 10 to 15. While in the x = 0 sample the structure is dominated by Q1 units linked to gallium in four-, five- and six-coordination, the gradual substitution of phosphate by tungstate significantly affects network reconstruction, eliminating P-O-P linkages, the concentration of which is found to be greatly diminished above the x = 10 level. While the structure of these glasses is dominated by Q0 units, connected to both gallium and tungstate species, 71Ga{31P} REDOR data suggest significant decreases in the extent of gallium-phosphorus connectivity with increasing Na2WO4 content. Finally, monotonic changes in both 23Na chemical shifts and 23Na-31P second moment values, M2(Na-P), indicate that the anionic surroundings of the sodium ions evolve from a pure phosphate to a mixed phosphate/tungstate environment.